The Lithuanianisation of Adam Mickiewicz - Viktorija Šeina (Interlitteraria)
In this article, I analyse the cultural practices applied by Lithuanian interwar intellectuals seeking to Lithuanianise the great Polish romantic poet Adam Mickiewicz. Mickiewicz was born to a family of Polish-speaking nobles in a predominantly Belarusian part of the former Grand Duchy of Lithuania. Because his historically themed works had an impact on the Lithuanian national movement, Lithuanian intellectuals sought ways to attribute Mickiewicz to Lithuanian culture.